THE REPRESENTATION OF VISUAL PERCEPTION IN ENGLISH AND UZBEK PROVERBS AND IDIOMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study explores the representation of visual perception in English and Uzbek proverbs and idioms, analyzing how both languages utilize visual metaphors to convey cultural values and shared human experiences. Through a comparative analysis, the research identifies common themes and unique expressions that highlight the role of visual perception in shaping linguistic expressions. The findings reveal that while both languages employ visual imagery to encapsulate wisdom and societal norms, cultural nuances influence the specific usage and interpretation of these expressions.